Persistent oral HPV infections – Are we vaccinating against the right HPV types to prevent HPV-related oropharyngeal cancer? - Annika Antonsson (Oral Oncology Reports)
HPV-related oropharyngeal cancers are increasing. These cancers are thought to be preceded by several years of persistent oral HPV infection. There is no current method for early detection of oropharyngeal cancers, but there are HPV vaccines available to prevent HPV infection. The vaccines are HPV type specific and will only protect against HPV types included in the vaccine. It is therefore important to identify HPV types that are found in persisting oral infections. This review looked at data from publications on persistent oral HPV infections and the HPV types causing these infections, with the HPV types included in the current preventative HPV vaccines available in mind.